PENGARUH SERVICE QUALITY TERHADAP LOYALITAS DENGAN KEPUASAN PELANGGAN SEBAGAI MEDIATOR DALAM INDUSTRI FARMASI B2B DI SUMATERA BARAT - Prima Budinewita; Eri Besra (Departemen Manajemen, 2020)
The purpose of this research is to determine the effect of job satisfaction on millennial employee performance with demographic variables as moderators. This research was conducted on PT Semen Padang millennial employees with a sample of 211 people. Research data processing was carried out by SEM-PLS. The results showed that aspects of job satisfaction that had a positive and significant effect on performance in the order of the greatest influence were job characteristics, communication, coworkers, and appreciation. While variable salary, promotion opportunities, supervisors, and fringe benefits are known to have no effect on performance. As for the variable procedures and work regulations found negative and significant effect. Furthermore, demographic variables moderate the relationship between satisfaction and performance. Performance that is influenced by aspects of job satisfaction was found to be different for work location, work period, and education variables.